2005
DOI: 10.1097/01.brs.0000181052.56604.30
|View full text |Cite
|
Sign up to set email alerts
|

Internal Strains in Healthy and Degenerated Lumbar Intervertebral Discs

Abstract: Increased nucleus pulposus migration in degenerated IVDs may result in increased shifting of the IVD pivot point during bending movements as well as intradiscal anular strains, particularly in the posterolateral anulus. This phenomenon may explain the segmental instability observed in degenerated segments as well as the associated anular tears present in the posterolateral region before IVD failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…Nuclear migration during bending subjects the anulus to tensile radial strains of up to 10%, depending on disc condition, region and bending modality [66]. Anulus deformation in response to such strains occurs by way of both transverse collagen bundle elongation and separation at lamellar interfaces [52].…”
Section: Functionmentioning
confidence: 99%
“…Nuclear migration during bending subjects the anulus to tensile radial strains of up to 10%, depending on disc condition, region and bending modality [66]. Anulus deformation in response to such strains occurs by way of both transverse collagen bundle elongation and separation at lamellar interfaces [52].…”
Section: Functionmentioning
confidence: 99%
“…Several in vivo studies of healthy individuals, employing magnetic resonance imaging (MRI), have reported IVD deformation in the sagittal and axial plane [13][14][15][16] and in scoliosis [17]. Limited data on NP deformation in lateral flexion exist mainly from cadaver studies [18]; however, no investigations to date have reported in vivo NP deformation in response to induced lateral flexion.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological loading condition of a NP could then be seen as a semi-confined situation. The NP is extremely deformable and it is not uncommon to observe strain amplitudes as large as 12.5% in physiological loading conditions (Tsantrizos et al, 2005). In parallel to its remarkable deformation property, in vivo experiments on baboon showed that removing the NP decreases the damping properties of the IVD (Quandieu et al, 1983).…”
Section: Introductionmentioning
confidence: 99%